2007
DOI: 10.1590/s0004-27302007000300014
|View full text |Cite
|
Sign up to set email alerts
|

Variabilidade do fenótipo de pacientes com síndrome de Noonan com e sem mutações no gene PTPN11

Abstract: RESUMOIntrodução: Aproximadamente 50% dos pacientes com síndrome de Noonan (SN) apresentam mutações em heterozigose no gene PTPN11. Objetivo: Avaliar a freqüência de mutações no PTPN11 em pacientes com SN e analisar a correlação fenótipo-genótipo. Pacientes: 33 pacientes com SN. Método: Extração de DNA de leucócitos periféricos e seqüenciamento dos 15 exons do P T P N 1 1. R e s u l t a d o s : Nove diferentes mutações m i s s e n s e n o P T P N 1 1, incluindo a mutação P491H, ainda não descrita, foram encont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 28 publications
1
2
0
Order By: Relevance
“…During the clonidine test to evaluate GH secretion, the patient had a GH peak of 8.5 µg/L, ruling out GH deficiency. These hormonal findings were similar to the ones observed in other NS patients in our group (30).…”
Section: Hormonal Analysissupporting
confidence: 92%
“…During the clonidine test to evaluate GH secretion, the patient had a GH peak of 8.5 µg/L, ruling out GH deficiency. These hormonal findings were similar to the ones observed in other NS patients in our group (30).…”
Section: Hormonal Analysissupporting
confidence: 92%
“…Several further studies confirmed PTPN11 as the most affected gene in NS patients and demonstrated a mutation frequency of 38–100 and 37–52% in individuals with familial and sporadic NS, respectively [7, 19, 27, 28]. …”
Section: Genetic Heterogeneity Of Noonan Syndromementioning
confidence: 99%
“…On the other hand, to determine the exact frequency of Noonan syndrome mutations, we excluded all data obtained from the screening of cohorts initially presenting with a particular condition (i.e., the mutational screening of Noonan syndrome patients with cardiac hypertrophy). The data gathered from the 82 included studies are summarized in Table 1 [77], [78], [79], [80], [81], [82], [83], [84], [85], [86], [87], [88], [89], [90], [91], [92], [93], [94], [95], [96], [97], [98], [99], [100], [101], [102], [103], [104], [105], [106], [107], [108].…”
Section: Reviewmentioning
confidence: 99%